Effect of Clausena excavata Burm. f. (Rutaceae) leaf extract on wound healing and antioxidant activity in rats - Albaayit SFA; Abba Y; Rasedee A; Abdullah N (Dove Medical Press, 2015)
Shaymaa Fadhel Abbas Albaayit,1,2 Yusuf Abba,3 Rasedee Abdullah,3 Noorlidah Abdullah1 1Institute of Biological Sciences, Faculty of Science, University of Malaya, Kuala Lumpur, Malaysia; 2Department of Biology, College of Science, University of Baghdad, Baghdad, Iraq; 3Department of Pathology and Microbiology, Faculty of Veterinary Medicine, Universiti Putra Malaysia, Serdang, Selangor, Malaysia Abstract: Clausena excavata is a well-known plant used in folkloric medicine for the treatment of different ailments. This study aimed to determine the in vitro cytoxicity of its leaf solvent extracts as well as the in vivo wound healing and antioxidant activities of the methanolic extracts of C. excavata (MECE). HaCaT (keratocyte) and Vero cell lines were used for evaluation of the in vitro cytotoxic effects, while the in vivo wound healing and antioxidant activities were determined in skin wounds inflicted on rats. Twenty adult male Sprague-Dawley rats were divided into five groups of four animals each. Approximately 3.14 cm2 excisional wound was inflicted on the nape of each rat following anesthesia. The treatment groups received topical application of MECE at 50 mg/mL (MECE-LD [low dose]), 100 mg/mL (MECE-MD [medium dose]), and 200 mg/mL (MECE-HD [high dose]), while the negative control group was treated with gum acacia in normal saline and the positive control group with intrasite gel. Wound contraction was evaluated on days 5, 10, and 15 after wound infliction, and tissue from wound area was collected at day 15 post-wound infliction for antioxidant enzyme evaluation and histopathological analyses. Generally, Vero cells were more resistant to the cytotoxic effects of the solvent extracts as compared with HaCaT cells. Chloroform (CH) and ethyl acetate (EA) extracts of C. excavata were toxic to HaCaT cells at 200 and 400 µg/mL, but the same concentrations showed higher (P<0.05) viability in Vero cells. There was significantly (P<0.01) greater wound contraction at days 10 and 15 post-wound infliction in all the treatment groups than in the control groups. Histopathologically, the MECE-HD-treated wound showed significantly (P<0.05) lesser inflammatory cell proliferation, degeneration, and distribution of granulation tissue than other groups. Similarly, the degree of collagen maturation, angiogenesis, and collagen distribution were significantly (P<0.05) lower in MECE-HD than in other groups. The MECE-HD, MECE-MD, and intrasite treatment groups showed a significantly (P<0.05) higher number of VEGF-positive and TGF-β1-positive cells in the skin wound than the control groups. The activities of superoxide dismutase and catalase were significantly (P<0.01) higher in the MECE-HD and intrasite treatment groups than in the other groups. Lipid peroxidase activity of the treated groups was significantly (P<0.01) lower than that in the control group. The study showed that MECE is a potent wound healing agent through anti-inflammatory and antioxidant effects that enhanced the rate of wound contraction, re-epithelialization, and collagen deposition. The effect of MECE is suggested to be due to its high polyphenolic compound content. Keywords: Clausena excavata, cytotoxicity, wound healing, antioxidant, histopathology, VEGF, TGF-β1